Research of oil mixture quality enriched with biogenic complex of plant ingredients - Нєміріч, Олександра Володимирівна; Вашека, Оксана Миколаївна; Петруша, Оксана Олександрівна; Карпенко, Анна (Eastern-European Journal of Enterprise Technologies, 2014)
Among the measures aimed at preservation of public health, prevention of emergence and spread of chronic non-contagious diseases, it is necessary and appropriate to create new food products, affordable to people, as well as corresponding to physiological norms of a human body and containing quite a high concentration of biologically valuable natural micronutrients. Butter-based oil mixtures are manufactured and sold at restaurant businesses and health resorts. The studies deals with improving their prescription content and increasing the nutritional value due to the harmonious combination of components and oil structure formation using plant raw materials, i.e. white sesame seeds and paprika powder. During microstructural studies of aqueous suspensions of crushed sesame seeds it was found that except sesame seed tissue particles the test samples contain structural elements with a globular and polyhedral structure. Dimensions of the structural elements vary from 1...15 to 4…40 microns respectively. The identified areas with the formation of different pattern structures and layers on the structural element surfaces prove that white sesame seeds are able of interacting with the aqueous phase significantly. The technology of a salt oil mixture was developed. The mixture is enriched with biogenic complex of plant supplements, by their optimal dosing in formulation: 4% of paprika powder, 20% of crushed white sesame seeds. The quality of the new oil mixture was studied. It was shown that according to the organoleptic qualities the enriched oil mixture is characterized by high flavor properties. Hardness, heat resistance and the structure ability to endure the liquid fat phase of the fresh oil-enriched mixture and during storage at +5 ºC for 7 days were studied. It was shown that the addition of crushed sesame seeds and paprika powder enables the formation of a complementary spatial network with a new coagulation bond between components of the oil mixture and supplements, and the formation of a structure with prominent thixotropic properties.